SOCIAL AND PEDAGOGICAL SUPPORT FOR INTERNALLY DISPLACED CHILDREN UNDER MARTIAL LAW - Protas, Oksana (Mountain School of Ukrainian Carpaty, 2022)
Millions of Ukrainian families with children have been forced to leave their permanent place of residence, moving to safer places under the current conditions of martial law in the country, which in its effects corresponds to the difficult life and often traumatic circumstances. The challenge arises in the need to meet the needs of new residents for social, medical, psychological, legal, social and pedagogical services, and appropriate living conditions. Forced moving can cause emotional and physical stress, fear, depression, inability to adequately assess events and make decisions, respond to them, and adapt to the changed conditions. The need for social protection and psychological and social and pedagogical assistance takes on increasing importance for families, in particular for children in difficult circumstances as a result of military actions. The article reveals the peculiarities of providing social and pedagogical support to children of internally displaced persons under martial law. The need for a multilevel comprehensive system of support for victims and displaced persons, the organization of intersectoral and interdepartmental interaction between specialists of corresponding services in providing complete psychological and social and pedagogical help, and coordination of efforts of various specialists is brought up to date. The need for social and pedagogical and psychological support for internally displaced children, which may require the recovery of their mental health and social well-being, an appropriate response to hostilities, and adaptation to new, changed conditions, is emphasized. It was established that social and pedagogical support is a type of activity of a social care teacher, aimed at organizing preventive and operational social and psychological and pedagogical assistance in preventing and overcoming situations that violate the vital activities of children. An analysis of models of social and pedagogical support for internally displaced children in difficult circumstances has been conducted. The technology of social and pedagogical support for children of internally displaced persons is considered. The relevant directions and content of social and pedagogical support for children of internally displaced persons under martial law are outlined. It is noted that modeling and organization of social and pedagogical support for children of internally displaced persons who suffered from military operations or were forced to leave their homes will help them to overcome the psychological trauma of military events, and will contribute to successful adaptation to the new changed conditions. Keywords: internally displaced persons, difficult life circumstances, social services, adaptation of internally displaced children, social and pedagogical support, model of social and pedagogical support for children of internally displaced families.